Fault location in electrical power systems using intelligent systems techniques. - Souza, J.C.S (IEEE Transactions on power delivery)
In this work an artificial neural network based methodology is proposed for power systems fault location. Several artificial neural networks are employed, each of them being responsible for detecting faults involving a limited number of components. The proposed methodology is tested using a test system and a real Brazilian system. Indexes based on the Hamming distance are also proposed for feature selection and analysis